Pengembangan Alat Peraga Listrik Searah pada Miniatur Rumah - Al Akbar, Amin; Syuwari, Hanifah Ridho; Muna, Nailul; Cholimah, Vina Nur; Maghfiroh, Adinda Haniatul; Kartika, Ika; Atika, Iva Nandya; Muadi, Muadi (Indonesian Journal of Learning and Educational Studies, 2023)
This study aims to develop a teaching aid in the form of miniature houses that explains the concept of series and parallel electrical circuits. This type of research is research and development research. Research and Development is a research method used to produce products, the product produced in this research is the manufacture of learning media. This research was said to be successful if the results obtained from the questionnaire were in the range of 3.26-4.00 and 2.56-3.25 or in very good and good criteria. In the material expert assessment, an average score of 3 was obtained in the good category, while in the media expert asessment, 2.22 was obtained in the poor category. So it can be concluded that conceptually the development of learning media in the form of a miniature house is able to explain series and parallel circuits in unidirectional electricity material. However, in the terms of feasibility and aesthetics, it is necessary to revise the appearance of the props.